008 Psychological Characteristics and Sexual Correlates of the Resolution Experience. (1st May 2022) - Rodrigues, I.; Porto, M.; Pimenta, F.; Costa, R.
ABSTRACT: Introduction: Resolution is least researched phase of the sexual response cycle. There is lack of knowledge of its psychological characteristics and correlates. Objectives: To develop a measure of depth of the resolution experience and explore its correlations with sexual functioning and intimate relationship quality. Method: The sample consisted of 475 respondents to an online survey (303 women, 172 men, mostly Portuguese). We used the Sexual Resolution Scale (SRS), which has eight items elaborated from the literature on resolution; the items refer to 1) experiencing profound peace, 2) deep relaxation, 3) heart rate acceleration, 4) intensified body awareness, 5) intensified emotions, 6) intensified imagination, 7) willingness to talk about emotionally charged subjects, 8) willingness to listen to emotionally charged subjects. Participants were asked to rate how intensely they had these experiences immediately after their last sexual encounter. Additionally, participants reported the intensity of desire, arousal, and orgasm, during the last sexual encounter, and completed the International Index of Erectile Function (IIEF-15), the Female Sexual Function Index (FSFI), the Female Sexual Distress Scale – Revised, and the Perceived Relationship Quality Components Inventory Results: A confirmatory factor analysis revealed that the SRS has two dimensions: Internal Experience (items 1 to 6) and Openness to Communication (items 7, 8). Both present good reliability. Invariance was confirmed between sexes. In women, Internal Experience and Openness to Communication correlated significantly with desire (rIE  = .52, rOC  = .24) and arousal (rIE  = .48, rOC  = .21) during last sexual encounter. Women's orgasm intensity during last sexual encounter correlated significantly with Internal Experience (rIE  = .28), but not with Openness to Communication (rOC  = .08, p = .148). Women's Internal Experience and Openness to Communication correlated significantly with better relationship quality (rIE  = .27, rOC  = .21), better sexual functioning (FSFI total score) (rIE  = .49, rOC  = .27), and less sexual distress (rIE  = -.35, rOC  = -.16). Men's Internal Experience and Openness to Communication correlated significantly with desire (rIE  = .38, rOC  = .26), arousal (rIE  = .40, rOC  = .32), and orgasm intensity, during last sexual encounter (rIE  = .46, rOC  = .26). Men's Internal Experience correlated significantly with better relationship quality (rIE  = .32) and IIEF-15 dimensions of intercourse satisfaction (rIE  = .41), sexual satisfaction (rIE  = .32), orgasmic function (rIE  = .20), and desire (rIE  = .20), but not with erectile function (rIE  = .06, p = .438). Men's Openness to Communication correlated significantly with better relationship quality (rIE  = .31), intercourse satisfaction (rIE  = .31) and sexual satisfaction (rIE  = .19), but not with erectile function (rIE  = -.08, p = .291), orgasmic function (rIE  = .10, p = .178), and desire (rIE  = .10, p = .211). Conclusions: The SRS has good psychometric properties and is valid for both sexes. This study emphasizes the twofold nature of resolution encompassing internal and relational experiences that are psychologically richer than a mere transition to an unaroused state, and subject to individual differences. Deeper resolution correlated with better sexual function and relationship quality. Disclosure: Work supported by industry: no.